Targeting eosinophils: severe asthma and beyond - Marco; Francesco; Lucia; Gianenrico (BioExcel Publishing Ltd, 2019)
Recent research in the field of bronchial asthma has mainly focused on eosinophilic disease phenotype. Several trials proved the efficacy and safety profile of eosinophils and interleukin (IL)-5 targeting molecules, currently approved for severe asthma and available on the market. They include mepolizumab and reslizumab, IL-5 blocking molecules, and benralizumab, targeting the IL-5 receptor and eliciting a NK cell-mediated antibody-dependent cellular cytotoxicity against eosinophils. Eosinophilic inflammation represents the common pathophysiological background of several conditions, providing the rationale for the use of the same biologics beyond asthma. Although with different evidence grade, from clinical trials to case reports, anti-IL-5 biologics have been investigated in eosinophilic granulomatosis with polyangitis, allergic bronchopulmonary aspergillosis, chronic eosinophilic pneumonia, nasal polyposis, hypereosinophilic syndrome, and eosinophilic esophagitis. However, non-negligible differences between asthma and other eosinophilic diseases, particularly in eosinophils homing (blood and/or tissues), target organs and thus clinical features, probably account for the different response to the same drug in different clinical conditions and highlights the need for tailoring the therapeutic approach by modulating the drug dose and/or by combination therapy with multiple drugs The optimal safety and tolerability profile of anti-IL-5 drugs warrants further and larger experimental and real-life investigations, which are needed especially in the field of non-asthma eosinophilic diseases. This review aims at summarizing the rationale for the use of biologics in eosinophilic diseases and their mechanisms of action. The current efficacy and safety evidence about eosinophils and IL-5 targeting molecules in asthma and in eosinophilic conditions beyond bronchi is also discussed.